Low sensitivity of the new FIGO classification system for electronic fetal monitoring to identify fetal acidosis in the second stage of labor - Frida Ekengård; Monika Cardell; Andreas Herbst (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2021)
Objective: In 2015, new FIGO guidelines for CTG interpretation were presented (FIGO-15). In 2017, the previous Swedish guidelines (SWE-09) were replaced with guidelines adapted to FIGOs (SWE-17). The performance of these three templates had not been scientifically evaluated before its clinical implementation. The objective of this study was to compare the sensitivity and specificity to detect fetal acidosis at birth using these three templates during the second stage of labor. Study design: This case-control study included 295 neonates with cord blood pH < 7.05 and 591 controls with pH ≥ 7.15, born 2012−2017. Tracings from the last 30−80 min of labor were classified independently by three assessors (midwives, residents and obstetricians), blinded to group and outcome. Results: The classification pathological using FIGO-15 had a sensitivity of 50 % and specificity of 88 % in detecting fetuses with acidosis. For SWE-17, the sensitivity was 62 % and the specificity 85 %. For SWE-09 the sensitivity was 87 % and the specificity 56 %.By combining suspicious and pathological patterns the sensitivity for FIGO-15 increased to 97 %, and for SWE-17 to 83 %, whereas the specificity decreased to 23 % and 68 % respectively. Conclusions: The FIGO classification seemed to be insufficiently discriminative in the second stage of labor; most patterns in acidotic cases were classified as merely suspicious with this template, and the sensitivity of pathological patterns was low at 50 %. Combined pathological and suspicious patterns detected fetal acidosis at a specificity that was too low to be useful (23 %). SWE-09 showed the best ability to detect acidosis with pathological patterns (sensitivity 87 %). SWE-17 reached almost the same sensitivity (83 %) with the combination of suspicious and pathological patterns, and at a higher specificity (68 %).